THEORETICAL CONSEQUENCE IN 2013 IN BENIN OF THE FIGHT AGAINST FUEL SELLERS OF CONTRABAND AND THE CONSUMERS' RENUNCIATION PRICE DIFFERENTIAL - KIKI, VINCENT JEAN-MARIE (My University, 2014)
Résumé: Cet article apparait juste comme une démonstration de la pertinence d’utilisation de la population des vendeurs d’essence de contrebande au Bénin comme champ d’application de nos travaux en statistique mathématique et applications à la CIPMA. En effet, il fallait expérimenter le modèle SBUC (Sampling By Use of Complicity) à l’aide d’un exemple de population cachée et réticente. Nous démontrons alors dans cet article que la lutte contre la vente de l’essence de contrebande avec son exacerbation en 2013 assortie de violence policière à finir par faire des vendeurs d’essence de contrebande, une véritable population cachée et réticente. Dès lors ce type de population constitue un cadre acceptable d’application de tout résultat d’échantillonnage de population cachée et réticente. C’est là le but essentiel de cet article. Abstract: This article presents the essential elements on the foundations and evolution of the crisis of the petroleum products commerce in Benin. After having tried without success to stop such commerce, the State has passed to the extreme during the years 2012 and 2013, putting the contribution in this struggle, soldiers, policemen and other. Then, the sellers of contraband petroleum products are henceforth more distrustful than ever with a big hostility to all kind of investigating about them. Finally, the article carries out an analysis of the behavior of the consumers of the contraband gas, in regard to the evolution of the differentials of price between the informal and formal sectors. Thanks to a threshold model, it was possible to conclude rightly or wrongly, that it exist a price differential between the formal and informal sectors, which is estimated at -45 F from which a customer of c is ready to give up to the benefit of the official sector.
Keywords: Fuel Sellers of Contraband; Fight Theoretical Consequence; The Consumers' Renunciation; Price Differential